Library Assessment & Decreasing Resources: Making Things Work - Newton Miller, Laura (Partnership, 2024)
This paper reviews how assessment has evolved in the past ten years at Carleton University in Ottawa, Ontario, Canada. From having 1.5 people devoted to assessment to one person in charge of assessment while also being Head of Collections, it became imperative to integrate assessment into the day-to-day workings of the library to address the lack of dedicated time available. By examining the library’s deployment of the Insync survey, reliance on external and internal university reports, assessment for strategic planning activities, and shifts in data collection practices, this paper will reveal how Carleton Library has reviewed the services, collection, and space given available resources. Partnering with other departments on campus and within the library is key.